STUDI KASUS PERASAAN BERSALAH (GUILTY FEELINGS) PELAKU PENYALAHGUNAAN NARKOBA DI LPKA TOMOHON - Rizaldy J. Illy; Tellma M. Tiwa; Marssel M. Sengkey (Program Studi Psikologi Universitas Negeri Manado, 2022)
Guilty Feelings According to Cohen, et al (2011) are positively and significantly related to religiosity and morals. Morals include feelings of guilt and remorse which are described as discomfort after engaging in deviant behavior. This study uses a qualitative approach with subject 1 who is a resident of the Tomohon Child Special Guidance Institute, a drug abuser. In the category of feelings of guilt proposed by Brue Narramore (2005), the subject is in the category of objective guilt, especially in the Legal Guilt where, the subject feels guilty because he has violated the law, which causes problems in the social environment.